A simple and reliable anion‐exchange resin method for sulfate extraction and purification suitable for multiple O‐ and S‐isotope measurements. (6th December 2016) - Le Gendre, Erwann; Martin, Erwan; Villemant, Benoit; Cartigny, Pierre; Assayag, Nelly
Abstract : Rationale: The O‐ and S‐isotope compositions of sulfates can be used as key tracers of the fate and sink of sulfate in both terrestrial and extra‐terrestrial environments. However, their application remains limited in those geological systems where sulfate occurs in low concentrations. Here we present a simple and reliable method to extract, purify and concentrate sulfate from natural samples. The method allows us to take into account the separation of nitrate, which is known to be an issue in O‐isotope analysis. Methods: The separation and concentration of sulfate from other anions in any aqueous solution are performed within a few hours via anion‐exchange resin. The possible O‐ (δ 18 O and Δ 17 O) and S‐ (δ 34 S, Δ 33 S and Δ 36 S) isotope exchanges, fractionations and/or contaminations are for the first time monitored during the whole procedure using initial O‐ and S‐mass‐dependent and mass‐independent sulfate solutions. Results: After elution in HCl, pure sulfate is fully retrieved and precipitated into BaSO4, which is suitable for O‐ and S‐isotopic measurements using established techniques. The analysis of retrieved barite presents no variation within 2σ uncertainties: ±0.5‰ and ±0.1‰ in O‐ (δ 18 O, Δ 17 O) and ±0.2‰, ±0.02‰ and ±0.09‰ in S‐ (δ 34 S, Δ 33 S and Δ 36 S) isotope ratios, respectively. Conclusions: This study shows that the resin method for sulfate extraction and purification, in addition to being cheap, simple and quick, is applicable for the measurements of all O‐ and S‐isotopic ratios in sulfates (including the Δ 17 O, Δ 33 S and Δ 36 S values). Therefore, this method can be easily used for a high range of natural samples in which sulfate occurs in low concentration including aerosols, ice cores, sediments, volcanic deposits, (paleo)soils and rainwater, and thus it can be a key to our understanding of the sulfur cycle on Earth. Copyright © 2016 John Wiley & Sons, Ltd.